论范晔《后汉书》群像列传之“论赞” = Study on Fan Ye’s “Lun” and “Zan” of selected collective biographies in history of Eastern Han - 关天辰 Guan, Tianchen (2016)
“论”、“赞”皆是史书中重要的体例，是表达史官史学观念的重要渠道，亦是映射著书之人文学功底的一面明镜。范晔《后汉书》群像列传中的《儒林传》、《文苑传》、《党锢传》的“论”与“赞”，体现出其“重学崇儒”的儒学观、“情采兼重”的文学观以及“以正一代得失”的史学观。Lun and Zan are both valuable and indispensable parts of Chinese historical records, which provide a gateway to express the author's views, and also reflect the author's compiling capability. This article focuses on “Lun” (comment) and “Zan” (compliment) of Biographies of Confucian Scholars儒林传, Biographies of Writers文苑传and Biographies of Partisan Prohibitions党锢传, to discuss Fan Ye's proposition on Confucianism, literature and historiography.